2002
DOI: 10.1021/cm020424n
|View full text |Cite
|
Sign up to set email alerts
|

A Sol−Gel Method Using Tetraethoxysilane and Acetic Anhydride:  Immobilization of Cubic μ-Oxo Si−Ti Complex in a Silica Matrix

Abstract: A sol-gel procedure using acetic anhydride as a substitute for water using a condensing reagent for the tetraethoxysilane (TEOS) to silica conversion is reported. The mixed solution obtained from the reaction of TEOS and acetic anhydride at 110 °C was allowed to stand in air for several weeks, resulting in gel formation of the solution. This prepared silica was mesoporous based on the nitrogen adsorption-desorption isotherms. Even when the gelation was performed in the presence of a large amount of benzene, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 90 publications
0
29
0
2
Order By: Relevance
“…Pande and Mehrotra found that the reaction between titanium isopropoxide and acetic anhydride yielded Ti‐ O ‐Ti bonds with the elimination of isopropylacetate . This nonhydrolytic anhydride route has later been used for the synthesis of silica and titania …”
Section: Chemical Formation Mechanismsmentioning
confidence: 99%
“…Pande and Mehrotra found that the reaction between titanium isopropoxide and acetic anhydride yielded Ti‐ O ‐Ti bonds with the elimination of isopropylacetate . This nonhydrolytic anhydride route has later been used for the synthesis of silica and titania …”
Section: Chemical Formation Mechanismsmentioning
confidence: 99%
“…These authors identified criteria which avoid the ligand exchange: Use of (i) non-coordinating solvents; (ii) small carboxylate ligands; and (iii) an electropositive metal alkoxide [43,44,87,88]. A high homogeneity was achieved in the ternary Ba−O−Si−O−Ti system [46], however later attempts to use this strategy for Zr−O−Si [45] and Ti−O−Si [38,89] systems suffered significantly from the ligand exchange, homocondensation and rather low homogeneity though the criteria suggested by Caruso Scheme 2. The targeted synthesis of single site vanadyl species on the surface and in the framework of silicate building block materials.…”
Section: New Materials By Ester Elimination: Silicophosphates and Thementioning
confidence: 99%
“…A high homogeneity was achieved in the ternary Ba-O-Si-O-Ti system [46], however later attempts to use this strategy for Zr-O-Si [45] and Ti-O-Si [38,89] systems suffered significantly from the ligand exchange, homocondensation and rather low homogeneity though the criteria suggested by Caruso and Hampden-Smith were followed. These problems may be overcome only if Ti is embedded in the starting precursor cubic µ-oxo Si-O-Ti complex which was probably preserved during its immobilization into the silica matrix [89]. Other less conventional transesterification pathways were used to prepare mixed oxides (e.g., reactions of Si(OEt) 4 with (MeO) 3 B 3 O 3 [90][91][92] and Ti(NO 3 ) 4 [93] producing B(OEt) 3 and EtONO 2 , respectively, as volatile reaction products), however the homogeneity of these materials was not studied in these cases.…”
Section: New Materials By Ester Elimination: Silicophosphates and Thementioning
confidence: 99%
See 1 more Smart Citation
“…These results support the elucidation of the catalytic cycle of the epoxidation using titanium catalyst including titanosilicates. Fujiwara et al (2002a) have also immobilized the cubic titanosiloxane 38 on a silica matrix For the preparation of the SiO 2 -TiO 2 mixed oxide with highly dispersed Ti atoms in a silica matrix, the cubic titanosiloxane 38 was an essential titanium source. This solid was an effective catalyst for the epoxidation of cyclohexene by TBHP.…”
Section: Heterogenization Of Homogeneous Catalystsmentioning
confidence: 99%